2013
DOI: 10.3892/or.2013.2785
|View full text |Cite
|
Sign up to set email alerts
|

IQGAP1 plays an important role in the cell proliferation of multiple myeloma via the MAP kinase (ERK) pathway

Abstract: The present study was designed to explore the role of IQ motif-containing GTPase activating protein 1 (IQGAP1) in the cell proliferation of multiple myeloma (MM) via the MAP kinase (ERK) pathway. Reverse transcription‑polymerase chain reaction (RT-PCR) and western blot analysis were carried out to evaluate the expression of IQGAP1 in RPMI8226, U266 and KM3 cell lines and in primary MM cells from 4 MM patients. shRNA-expressing plasmids were used in RPMI8226 cells to knock down IQGAP1 and an MTT assay was used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 34 publications
3
7
0
Order By: Relevance
“…In this study we examine a novel approach to disrupt the interaction between IQGAP1 and MAPK and determine the biologic effects of RAS/MAPK signaling on MM self-renewal. We found that IQGAP1 knockdown inhibited RAS/MAPK signaling as has been previously been shown (29, 30). Moreover, targeting IQGAP1 with a small peptide mimetic that binds to ERK also effectively blocked MAPK signaling, decreased clonogenic growth and self-renewal in vitro , and inhibited MM tumor initiating cell frequency of NCI-H929 cells engrafted in immunodeficient mice.…”
Section: Introductionsupporting
confidence: 87%
See 1 more Smart Citation
“…In this study we examine a novel approach to disrupt the interaction between IQGAP1 and MAPK and determine the biologic effects of RAS/MAPK signaling on MM self-renewal. We found that IQGAP1 knockdown inhibited RAS/MAPK signaling as has been previously been shown (29, 30). Moreover, targeting IQGAP1 with a small peptide mimetic that binds to ERK also effectively blocked MAPK signaling, decreased clonogenic growth and self-renewal in vitro , and inhibited MM tumor initiating cell frequency of NCI-H929 cells engrafted in immunodeficient mice.…”
Section: Introductionsupporting
confidence: 87%
“…Previous studies have shown that IQGAP1 expression is required for RAS/MAPK signaling and cell growth both in solid tumor models and in MM (24, 29, 30). However, it is not known whether IQGAP1 loss-of-function mimics the cell cycle arrest observed with direct MAPK pathway inhibition in MM (19, 21, 39).…”
Section: Resultsmentioning
confidence: 99%
“…The ERK pathway typically transduces growth factor signals that lead to cell differentiation or proliferation (7); however, the association of ERK with CaA-induced improvement of cell viability and subsequent protection against DNA damage is unclear. We exposed L-02 cells to 10 μM CaA for 0, 3, 6, 12, or 24 h, and found that with increased time of CaA exposure, there was enhanced expression of p-ERK, a biomarker for the activation of ERK signaling (Figure 4A and B).…”
Section: Resultsmentioning
confidence: 99%
“…MAPKs including ERK, p38 MAPK, and JNK are key components of signaling pathways that control cell differentiation and growth (9,30,31). There is evidence that MAPKs can be phosphorylated and activated in response to oxidant-induced alterations of the redox state (7). After activation, each MAPK phosphorylates a distinct spectrum of substrates including key regulatory enzymes, cytoskeletal proteins, regulators of apoptosis, nuclear receptors, and many transcription factors that bind to specific DNA sequences and induce transcriptional activation and DNA synthesis, with cellular recruitment to the S-phase (9,30,32).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation